Effect of the 3q26-coding oncogene SEC62 as a potential prognostic marker in patients with ovarian neoplasia - Radosa, Julia C.; Kasoha, Mariz; Schilz, Anne-Christine; Takacs, Zoltan F.; Kaya, Askin; Radosa, Marc P.; Linxweiler, Barbara; Linxweiler, Maximilian; Bohle, Rainer M.; Wagner, Mathias; Wagenpfeil, Gudrun; Solomayer, Erich-Franz; et al. (Frontiers in Physiology, 2023)
With approximately 220,000 newly diagnosed cases per year, ovarian cancer is among the most frequently occurring cancers among women and the second leading cause of death from gynecological malignancies worldwide. About 70% of these cancers are diagnosed in advanced stages (FIGO IIB–IV), with a 5-year survival rate of 20–30%. Due to the poor prognosis of this disease, research has focused on its pathogenesis and the identification of prognostic factors. One possible approach for the identification of biological markers is the identification of tumor entity-specific genetic “driver mutations”. One such mutation is 3q26 amplification in the tumor driver SEC62, which has been identified as relevant to the pathogenesis of ovarian cancer. This study was conducted to investigate the role of SEC62 in ovarian malignancies. Patients with ovarian neoplasias (borderline tumors of the ovary and ovarian cancer) who were treated between January 2007 and April 2019 at the Department of Gynecology and Obstetrics, Saarland University Hospital, were included in this retrospective study. SEC62 expression in tumor tissue samples taken during clinical treatment was assessed immunohistochemically, with the calculation of immunoreactivity scores according to Remmele and Stegner, Pathologe, 1987, 8, 138–140. Correlations of SEC62 expression with the TNM stage, histological subtype, tumor entity, and oncological outcomes (progression-free and overall survival) were examined. The sample comprised 167 patients (123 with ovarian cancer and 44 with borderline tumors of the ovary) with a median age of 60 (range, 15–87) years. At the time of diagnosis, 77 (46%) cases were FIGO stage III. All tissue slides showed SEC62 overexpression in tumor cells and no SEC62 expression in other cells. Median immunoreactivity scores were 8 (range, 2–12) for ovarian cancer and 9 (range, 4–12) for borderline tumors of the ovary. Patients with borderline tumors of the ovary as well as patients with ovarian cancer and an immunoreactive score (IRS) ≤ 9 showed an improved overall survival compared to those presenting with an IRS score >9 (p = 0.03). SEC62 seems to be a prognostic biomarker for the overall survival of patients with ovarian malignancies.